Mismatch Negativity in Children and Adolescents with Autism Spectrum Disorder - Mayerle, Maria Clara Clack da Silva; Riesgo, Rudimar; Gregory, Letícia; Borges, Viviann Magalhães Silva; Sleifer, Pricila (International Archives of Otorhinolaryngology, 2023)
Introduction Individuals with autism spectrum disorder (ASD) have abnormalities in auditory perception and sensitivity. The mismatch negativity (MMN) component of the evoked potential demonstrates a brain detection response to an auditory change due to memory, and enables the identification of changes in the auditory system.Objective To analyze MMN responses in children and adolescents with ASD and compare them with those of a control group.Methods Cross-sectional and comparative study. The sample was composed of 68 children and adolescents, divided into study group (SG), which contained those diagnosed with ASD, and the control group (CG), which contained those with typical development, normal hearing thresholds, and without hearing complaints. All participants were submitted to peripheral and central electrophysiological auditory evaluations. For the electrophysiological auditory evaluation and MMN recording, the electrodes were fixed in the following positions: Fz (active electrode), M1 and M2 (reference electrodes), and on the forehead (ground electrode). Auditory stimuli were presented in both ears simultaneously, with a frequency of 1,000 Hz for the frequent stimulus, and of 2,000 Hz for the rare stimulus, in an intensity of 80 dBNA.Results Latency and amplitude values were increased in the SG, with a statistically significant difference in comparison with the CG. In the MMN analysis, there was no statistically significant difference in the comparison between right and left ears and between genders.Conclusion Children and adolescents with ASD had higher latency and amplitude values in the MMN component than the individuals in the CG.
Keywords: autism spectrum disorder; auditory evoked potentials; electrophysiology; auditory perception; child; audiology